PEER TUTORING IN THE ELEMENTARY CLASSROOM: PUTTING (A) THEORY INTO PRACTICE - Russo, James Anthony (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
This essay explores how elementary school teachers can support students in becoming effective peer tutors. Drawing on the author’s personal experience as an elementary educator and researcher, it discusses how cognitive load theory can be used to generate a framework to support practicing teachers in implementing peer tutoring in their own classrooms. The framework presented is particularly relevant to well-structured learning domains, such as mathematics. TUTORAT PAR LES PAIRS : DE (LA) THÉORIE À LA PRATIQUE Cet essai s’intéresse aux moyens que possèdent les enseignants du primaire pour aider leurs élèves à devenir des tuteurs efficaces pour leurs pairs. En se basant sur son expérience personnelle comme enseignant et chercheur au primaire, l’auteur présente la manière dont la théorie de la charge cognitive peut être utilisée en classe pour créer un cadre soutenant les enseignants dans l’implémentation du tutorat par les pairs dans leur classe respective. Le cadre présenté se révèle particulièrement pertinent pour les domaines d’apprentissage très structurés, comme les mathématiques.